2021
DOI: 10.1002/aesr.202000097
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress of the Design and Engineering of Bismuth Oxyhalides for Photocatalytic Nitrogen Fixation

Abstract: Photocatalytic nitrogen fixation represents an effective technology for the artificial production of ammonia from atmospheric nitrogen, a critical step toward a sustainable economy. Bismuth oxyhalides (BiOX, X ¼ Cl, Br, and I) have emerged as viable catalysts for photocatalytic reduction of nitrogen into ammonia, due to their unique electronic structures and optical properties. Herein, the recent progress of BiOX-based photocatalysts for nitrogen fixation, with a focus on the reaction mechanism and pathways, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 241 publications
0
3
0
Order By: Relevance
“…Transition metal oxyhalides have been widely used as Li-ion cathodes and photocatalysts because of their advantageous electrochemical/physical properties. Li and co-workers fabricated NiFeO x F y nanosheets and found dramatic activation of the OER activity and increase of the redox current. Using in situ Raman, ex situ XPS spectra of O 1s and F 1s, and in situ XAFS, Li and co-workers found that fluorine in NiFeO x F y gradually disappeared and enabled facile formation of defective and Fe-enriched Ni­(Fe)­O x H y as the active species.…”
Section: Materials With Structural Transformation In Oer Electrocatal...mentioning
confidence: 99%
“…Transition metal oxyhalides have been widely used as Li-ion cathodes and photocatalysts because of their advantageous electrochemical/physical properties. Li and co-workers fabricated NiFeO x F y nanosheets and found dramatic activation of the OER activity and increase of the redox current. Using in situ Raman, ex situ XPS spectra of O 1s and F 1s, and in situ XAFS, Li and co-workers found that fluorine in NiFeO x F y gradually disappeared and enabled facile formation of defective and Fe-enriched Ni­(Fe)­O x H y as the active species.…”
Section: Materials With Structural Transformation In Oer Electrocatal...mentioning
confidence: 99%
“…These structural and electronic characteristics make BiOXs suitable for photocatalysts. The heterojunction of BiOX/BiOY (where X, Y = Cl, Br and I; X ≠ Y) effectively adjusted the band gap energy and increased the visible-light absorption capability, enhancing the photocatalytic activity of single-component BiOX. , The heterojunction, especially BiOBr/BiOI, achieves the fast transfer of electrons and holes, suppresses the recombination of electron–hole pairs, and enhances photocatalytic activity . Accordingly, the nanoscale BiOX and BiOX/BiOY photocatalysts under sunlight irradiation have been reported. , …”
Section: Introductionmentioning
confidence: 99%
“…41,58 Consequently, for selective NRR, the ideal catalysts of OIP QDs should be further designed with (1) a lower d-band state to weaken H adsorption and (2) abundant electron deficient sites with strong N 2 affinity. 54,59–61…”
Section: Introductionmentioning
confidence: 99%
“…41,58 Consequently, for selective NRR, the ideal catalysts of OIP QDs should be further designed with (1) a lower d-band state to weaken H adsorption and (2) abundant electron deficient sites with strong N 2 affinity. 54,[59][60][61] Herein, a water-resistant OIP QDs was rapidly prepared by the one-step ESI-based microdroplet synthesis in microseconds, termed as polycarbonate (PC)-part-encapsulated Zn, Pt IV -codoped PbO-MAPbBr 3 heterojunction (Pt IV /Zn/PbO/ PC-Zn/MAPbBr 3 ). During the fast ESI, the core of Zn/MAPbBr 3 was crystallized, followed by PC encapsulation to obtain good water-resistance without environmental pollution.…”
Section: Introductionmentioning
confidence: 99%